MicroRNAs in normal and cancer cells: a new class of gene expression regulators - Bagnyukova, T.V.; Pogribny, I.P.; Chekhun, V.F. (Experimental Oncology, 2006)
MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at posttranscriptional level. They are involved in cellular development, differentiation, proliferation and apoptosis and play a significant role in cancer. This review describes miRNA biogenesis, their functions in normal cells, and alterations of miRNA sets in cancer and roles of antitumorigenic and oncogenic miRNAs in cancer development.